1985
DOI: 10.3758/bf03198452
|View full text |Cite
|
Sign up to set email alerts
|

On visual access to letter case and lexical/semantic information

Abstract: Four experiments were designed to investigate automatic processing of letter case and lexical/semantic information under forward and backward masking conditions that disallowed a visible image. Stimulus displays were letter string pairs; the letter case for each pair matched or mismatched, and the relationship between the two strings within pairs varied. Experiment 1 required direct Same-Different responses to stimulus pairs, and the results indicate that tasks requiring direct responses to stimulus inputs can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
3

Year Published

1988
1988
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 31 publications
1
16
3
Order By: Relevance
“…Low-frequency words thus seem to appear for a shorter duration than high-frequency words. These results occur with exposure durations sufficient to allow the identification of the words; with much shorter, or with pattern-masked, exposures, the results are not invariably the same (Avant & Lyman, 1975;Avant & Theiman, 1985) and may reflect very early processing factors. Hochhaus et al (1991) used a Likert-type scale of I to 4, with 1 = shortest judged duration and 4 = longest.…”
mentioning
confidence: 60%
“…Low-frequency words thus seem to appear for a shorter duration than high-frequency words. These results occur with exposure durations sufficient to allow the identification of the words; with much shorter, or with pattern-masked, exposures, the results are not invariably the same (Avant & Lyman, 1975;Avant & Theiman, 1985) and may reflect very early processing factors. Hochhaus et al (1991) used a Likert-type scale of I to 4, with 1 = shortest judged duration and 4 = longest.…”
mentioning
confidence: 60%
“…Semantic priming is a measuring instrument that influences what it is measuring. Some other kind of indirect measurement is needed if the semantic properties of early automatic encoding are to be explored (e.g., Avant & Thieman, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Duration as an Indirect Measure Given the proposed methodological criteria, there are certain limitations as to the direct and indirect measures that can be used successfully to investigate the relation between consciousness and perception. However, a recent series of experiments reported by Avant and Thieman (1985) suggests a possible approach. These investigators claimed to have demonstrated that judgments of apparent visual duration provide an indirect measure of perceptual processing that is more sensitive to the lexical status of a visual stimulus than are direct discriminative responses.…”
Section: Application: Judgment Of Apparent Visualmentioning
confidence: 99%
“…The only assumption required by the proposed approach is that the sensitivity of direct discriminations to relevant conscious information is greater than or equal to the sensitivity of comparable indirect discriminations. The proposed approach is illustrated through an evaluation of Avant and Thieman's (1985) recent claim that an indirect measure of perception based on judgments of apparent visual duration provides a more sensitive indicator of perception than does a direct measure based on forced-choice recognition. Contrary to this claim, when direct and indirect indexes are measured under comparable conditions, an indirect measure based on judgments of perceived duration provides a less sensitive index of perceptual processing than do comparable direct measures.…”
mentioning
confidence: 99%
See 1 more Smart Citation